The Campus Canopy,1942-04-24 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1942)
The Campus Canopy,April, 24, 1942. Vol. 8, No. 18. -- O’Neal And Whitaker Head Pine Cone Staff -- 3 Seniors, 10 Juniors, and 1 Sophmore To Be Given Emblems for Leadership -- Bond Committee Sponsors Sale Sat. -- May Day-Play Day Committees Are Named By Ivey And McRee -- Seniors To Attend Opera In Atlanta -- Senior Recitals Begin Next Month -- Scoop-Of-The-Year-Book -- Drew and Carter Begin New Classes In Defense Work -- Brookwood Park Is Vesper Setting
Digitized from original print, Valdosta State University Archives and Special Collections, February 15, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; Valdosta State College; Valdosta State University; VSC; VSU; 1940s; 1942; GSWC